The Effect of Prolonged Irrigation on the Dry Steppe Soils’ Fertility in the Volga Region - Anatolyevna Pronko, Nina; Vladislavovich Korsak, Viktor; Gennadievna Romanova, Lubov; Vladimirovich Kravchuk, Aleksey; Viktorovich Afonin, Vladimir (International Journal of Engineering and Technology, 2018)
The article deals with the negative effect of the prolonged irrigation on the contents and quality of humus, and plant nutrientsâ€™ stock in theÂ soil. TheÂ research was aimed at studying the nature and regularities of theÂ transformation of organic matter (humus) and nutrients in the dark chestnut soil of dry steppe zone in the Volga region in the process of irrigation over half aÂ century long. Field and laboratory experiments, as well as theoretical methods, such as mathematical statistics were used for studying the soil agrochemical properties. The research has shown that humus mineralization in irrigated soils is more pronounced, compared to nonirrigated soils, dehumification increases with increasing the period of irrigation and intensification of agriculture; the content and stock of humus decreases with irrigation, and is accompanied by the negative changes in its qualitative composition. The article describes the reasons for dehumification and negative changes in the qualitative composition of humus in the dark chestnut soils: deficient nitrogen balance due to insufficient use of nitrogen fertilizers, which resulted in the destruction of the organic matter in the soil, increased share of tilled crops in the crop structure, absence of nitrogen-fixing ability in alfalfa due to significant soil compaction, and insufficient introduction of organic fertilizers. The found peculiarities of dehumification and reduction of nutrients availability in the soil, which are the most dangerous degradation processes in the soils of the region that reduce the efficiency of irrigated agriculture, are required for developing substantiated solutions for preventing dehumification, restoring the fertility of irrigated soils, and reducing deficiency of foodstuffs in arid regions. Â Â